Validation of portable electronic equipment (Accutrend® Plus) to determine glucose, total cholesterol, and triglycerides in rats (Rattus) and dogs (Canis lupus familiaris) - Ramírez, Paola de la Paz; Ordaz, Gerardo; Gonzáles, Reynaldo de la Paz; Pérez, Rosa Elena; López, Manuel; Ortiz, Ruy (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study aimed to validate the analytical precision of the Accutrend® Plus portable electronic equipment (PE) to determine glucose (GLU), total cholesterol (TC), and triglycerides (TG) in rats and dogs using the conventional laboratory method (CM) as a reference. Materials and Methods: To determine the analytical accuracy of the Accutrend® Plus in the measurement of GLU, CT, and TG. The EP-9-A2 guide (Clinical and Laboratory Standards Institute), Bland-Altman graphical analysis, and Lin’s correlation coefficient of concordance (CCC) were implemented. Results: The average differences (p > 0.05) between PE and CM for GLU, TC, and TG were 2.21, 1.20, and 0.72 mg·dl−1, respectively, in rats and 1.06, 4.30, and 2.41 mg·dl−1, respectively, in dogs (p > 0.05). Both methods showed a linear relationship with Pearson’s correlation coefficients > 0.96 and R2 > 0.97 for the three biochemical indicators evaluated in both species. The GLU, TC, and TG values obtained by the PE were substantial, as evident from Lin’s CCC > 0.96. Conclusion: The PE Accutrend® Plus is potent for monitoring GLU, TC, and TG in rats and dogs because of its precision and ability to facilitate measurement by reducing stress in animals during sampling. J. Adv. Vet. Anim. Res., 10(1): 57–63, March 2023 http://doi.org/10.5455/javar.2023.j652